Grazing regime rather than grazing intensity affect the foraging behavior of cattle - You Wang; Rui Yu; Xin Li; Ronghao Chen; Jiahui Liu (Ecological Informatics)
Foraging behavior of cattle is a critical factor for sustainable grassland grazing. Investigating cattle's behavior under varying grazing strategies can offer valuable insights into the interactions between grazing animals and grasslands. In this study, we used a fenced grazing experiment to test the hypothesis that grazing pressure influences the grass patches by altering the foraging behavior of cattle. Cattle location trajectories were tracked using Global Positioning System collars, and livestock behavior was simultaneously observed and recorded in the field. Five machine learning models—XGBoost, Random Forest, Decision Tree, Extra Trees, and CatBoost—were employed to classify cattle's behavior and to assess the impact of grazing strategies on these behaviors. The effects of grazing strategies on grassland vegetation were analyzed based on spatial remote sensing data acquired from unmanned aerial systems (UAS). The main findings were: (1) the XGBoost classification model has outperformed the others models, with an average accuracy of 0.947; (2) grazing intensity only significantly affected standing behaviors, while grazing regime significantly influenced foraging, walking, standing, ruminating, and resting behaviors; (3) increased grazing intensity had led to a larger proportion of areas with declining normalized difference vegetation index (NDVI) in the study area; however, the proportion of areas with increased NDVI was consistently higher in rotationally grazed regions compared to that of continuously grazed areas; (4) The changes in NDVI were significantly positively correlated with foraging probability in continuously grazed plots; however, NDVI changes in lightly grazed rotational areas had a weak correlation with foraging probability. These results suggest that proper management strategies, such as rotational grazing can enhance grassland health, which provides a scientific foundation and technical support for the development and implementation of sustainable grassland management strategies.